Characterization of Two Hydrogen-Oxidizing Hydrogenovibrio Strains From Kermadec Volcanic Island Arc Hydrothermal Vents - Sass, Katharina; Perner, Mirjam (Frontiers in Marine Science, 2020)
The genus Hydrogenovibrio consists of chemolithotrophic sulfur- and hydrogen-oxidizing bacteria that are found in diverse marine environments including hydrothermal vents where they can reach high cell numbers. Although several vent Hydrogenovibrio genomes encode for [NiFe]-hydrogenases (enzymes catalyzing the reversible reaction of hydrogen into protons and electrons), different attempts to grow these strains on hydrogen failed for a long time. Not long ago it was shown that some Hydrogenovibrio strains from hydrothermal vents are indeed able to oxidize hydrogen, which broadens their physiological spectrum in a competitive environment for energy sources. We here identify two active hydrogen consuming bacteria of the Hydrogenovibrio genus with different hydrogenase genes from vents in the South Pacific Ocean. Based on our results, hydrogen consuming Hydrogenovibrio species seem to be much more widespread in the oceans than expected.